The Influence of TikTok Social Media on Customer Loyalty: Evidence from HMNS Perfume on TikTok Shop - Padju, Muhammad Gifari Benevi; Susanti, Ety Dwi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of TikTok social media on customer loyalty toward HMNS perfume products through the TikTok Shop feature. Unlike previous studies that predominantly emphasized purchase intention or brand awareness, this research highlights customer loyalty as a strategic outcome of TikTok-based marketing in Indonesia, where social commerce adoption is rapidly expanding. The research employed a quantitative method with an online survey of 120 respondents who had purchased HMNS perfumes via the TikTok Shop. The data were analyzed using simple linear regression, t-test, F-test, and classical assumption tests with the help of SPSS. The results indicate that TikTok social media has a positive and significant effect on customer loyalty (β = 0.791, t = 10.068, p < 0.001; F = 101.357, p < 0.001). Customer loyalty is reflected in repeat purchase behavior, strong brand preference, and willingness to recommend HMNS perfumes to others. The novelty of this study lies in its focus on strengthening loyalty to a local perfume brand in the TikTok Shop ecosystem, a context that remains underexplored in Indonesia. Theoretically, this research expands Oliver’s (1999) loyalty framework within social commerce. Practically, the findings provide managerial insights for local brands to optimize creative content, influencer collaboration, and live shopping strategies to remain competitive in the digital economy, which is aligned with Indonesia’s 2045 Golden Vision.